Physical incompatibility of mixing of insecticides and fungicides - Petter, Fabiano André; Segate, Diego; Almeida, Fernandes Antônio de; Alcântara Neto, Francisco; Pacheco, Leandro Pereira (Comunicata Scientiae, 2013)
The objective of this study was to evaluate the physical interaction between simulated tank mixtures of different classes of pesticides. The treatments consisted of mixtures of six insecticides (methomyl, chlorpyrifos, teflubenzuron, triflumuron, cypermethrin and cyhalothrin + thiamethoxam) with six fungicides (pyraclostrobin/epoxiconazole, trifloxystrobin/tebuconazole, carbendazin, flutriafol, azoxystrobin/cyproconazole, flutriafol/tiofanato- methyl) in the absence and presence of two pH reducers (Pyroligneous acid and boric acid) with four replications. We used a scale from 1 to 5 to evaluate the degree of mismatch, where 1 is the immediate separation of the mixture and it is recommended not to apply is 5 and the homogeneity of the mixtures without restrictions apply. The major physical incompatibilities in mixtures of insecticides and fungicides were observed in the presence of the insecticides chlorpyrifos, cypermethrin, thiamethoxam/lambda-cyhalothrin and the insecticides physiological teflubenzuron, triflumuron and the fungicide pyraclostrobin/ epoxiconazole, azoxystrobin/cyproconazole and flutriafol/thiophanate-methyl. Pyroligneous acid and boric acid showed to be good alternatives such as reducing the pH in the preparation of spray mixtures spraying of insecticides with fungicides. Should be avoided tank mixtures of chlorpyrifos, and teflubenzuron triflumuron with all fungicides tested.